2015
DOI: 10.3390/en81012080
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting China’s Annual Biofuel Production Using an Improved Grey Model

Abstract: Biofuel production in China suffers from many uncertainties due to concerns about the government's support policy and supply of biofuel raw material. Predicting biofuel production is critical to the development of this energy industry. Depending on the biofuel's characteristics, we improve the prediction precision of the conventional prediction method by creating a dynamic fuzzy grey-Markov prediction model. Our model divides random time series decomposition into a change trend sequence and a fluctuation seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Compared with the conventional grey model, the improved grey model has a higher forecast accuracy, as it is able to optimize the initial condition and predict both direct and iterative manners [21][22][23][24][25][26]. The nonhomogeneous discrete grey model can better capture nonhomogeneous effects on the data [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared with the conventional grey model, the improved grey model has a higher forecast accuracy, as it is able to optimize the initial condition and predict both direct and iterative manners [21][22][23][24][25][26]. The nonhomogeneous discrete grey model can better capture nonhomogeneous effects on the data [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, the grey-fuzzy-Markov pattern recognition model has rarely been employed to improve forecasting and prediction of industrial accidents in industrial organisations. The authors found a number of papers applying only grey-fuzzy-Markov (Asrari et al 2012;Geng et al 2015) in the scientific literature with limited applications to the analysis of electrical and biofuel production, for instance. Industrial accident forecasting has not been tackled in grey-fuzzy-Markov literature.…”
Section: Related Literaturementioning
confidence: 99%
“…GFM models have been developed based on the understanding that hybrid models have greater forecasting potentials than single evaluation models (Li and Li 2015). GFMs have found applications in areas such as electrical load analysis (Asrari et al 2012) and biofuel production (Geng et al 2015). The grey aspect of the GFM has its major focus on uncertainty inherent in sparsely available information (Deng 1982;Liu 2011).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Grey models are powerful estimation tools to deal with partially unknown systems [17][18][19][20][21]. In this research, the grey prediction model has been built to estimate the ICE coming modes once the machine is repeatedly operated with the same cycle.…”
Section: Grey Prediction Modelmentioning
confidence: 99%